Gut microbiota dysbiosis, sarcopenia, osteoporosis and osteosarcopenia in older people: A systematic review protocol - Nailton José Neto; Mário Duarte Brito; Cristiano dos Santos Gomes; Luana Caroline de Assunção Cortez Corrêa; Gerlane Coelho Bernardo Guerra; Ricardo Oliveira Guerra (PLoS ONE, 2025)
Introduction Sarcopenia and Osteoporosis are two prevalent conditions in the older population and are defined by low strength, muscle quality/volume and low Bone Mineral Density, respectively. When there is a concomitant presence of both, there is a novel musculoskeletal condition called Osteosarcopenia. These conditions adversely affect quality of life and elevate the risk of fractures, disability, and mortality among older individuals. Dysbiosis of the gut microbiota is the impairment of the mutualistic relationship between microorganisms, metabolic products and the host’s immune system. Gut microbiota dysbiosis could be intricately linked to sarcopenia and osteoporosis, shedding light on the complex microbiota-gut-bone-muscle axis. Furthermore, the intestinal microbiota experiences a notable decline in beneficial microorganisms as part of the aging process. The relationship between dysbiosis of the intestinal microbiota in older people and sarcopenia, osteoporosis or osteosarcopenia is still unclear. This review protocol aims to systematically review the literature and compile evidence on the influence of gut microbiota dysbiosis on musculoskeletal function in older people with sarcopenia, osteoporosis or osteosarcopenia. Methods/Analysis This systematic review will analyze observational studies that have investigated the relationship between the effects of gut microbiota dysbiosis and sarcopenia, osteoporosis and osteosarcopenia in older people aged 65 and over. Studies will be retrieved from PubMed/MEDLINE, EMBASE, Scopus, Web of Science and the Cochrane Library. Outcome measures will include body composition for diagnosing osteoporosis and screening for sarcopenia/osteosarcopenia by any criteria. Data synthesis will involve quantitative analysis using summary measures. If sufficient studies, homogeneity and heterogeneity analysis will be performed to conduct Meta-analysis and pooled OR, RR and HR measures will be provided.